Estudo do potencial antiinflamatório do óleo-resina da Copaifera langsdorffii Desf. (COPAÍBA) e de seu constituinte diterpênico ácido kaurenóico nos modelos experimentais de inflamação intestinal - Paiva, Laura Andréa Farias (2004)
Copaiba oil-resin from Copaifera langsdorffii (Leguminaceae) is a reputed traditional remedy for the treatment of inflammatory conditions and to promote healing of ulcers and wounds. Previous studies established its anti-inflammatory and gastroprotective properties through animal experimentation. The present study extended these earlier studies to analyse the intestinal anti-inflammatory potential of oil-resin Copaifera langsdorffii (ORCL) and its diterpene constituent, kaurenoic acid (KA) in rat models of ulcerative colitis induced by acetic acid (AA-UC), and trinitribenzene sulfonic acid (TNBS-UC), and in indomethacin -and ischemia-reperfusion-induced intestinal inflammation (IND-II and I/R-II). Further, its wound healing potential was evaluated in rats on open and incision wounds. Rats were pretreated orally (15 hrs and 2 hrs before) or rectally 2 hrs before the induction of colitis with ORCL (200 and 400 mg/kg), KA (50 and 100 mg/kg) or vehicle (1 ml, 2% Tween 80 or 1 ml, 2% DMSO). Colitis was induced by intracolonic instillation of a 2 ml of 4% (v/v) acetic acid solution or TNBS (0.25 ml of 20 mg) and 24 hrs or 72 hrs latter, the colonic mucosa was analysed for the severity of macroscopic colonic damage, the myeloperoxidase and the malondialdehyde levels. In AA-UC model, a marked reduction in Gross damage score and in wet weight/length ratio of colonic tissue were evident in animals pretreated orally or rectally with test substances, as compared to vehicle alone-treated controls. This effect was confirmed biochemically by a significant reduction in colonic myeloperoxidase (MPO) activity, the marker of neutrophilic infiltration and by a marked decrease in malondialdehyde (MDA) level, an indicator of lipoperoxidation. Besides, AA elevated increase in the levels of nitrite and catalase activity in colon tissue was also significantly decreased by ORCL treatment. Furthermore, microscopical examination revealed the diminution of inflammatory cell infiltration, and the submucosal edema in colon segments of rats pretreated with ORCL or KA. In a similar manner, in TNBS-UC, a marked reduction in Gross damage score and in wet weight/length ratio of colonic tissue was evident by ORCL pretreatment (400 mg/kg, p.o. or intra-rectal) at 2, 24 and 48 hrs after intracolonic injection of TNBS. MPO activity but not the MDA and catalase levels were significantly affected by ORCL treatment. Histological observations also indicated only a partial protection by ORCL, suggesting that TNBS-UC being a chronic model, a more prolonged therapy may be needed. In the model of I/R-II, five forty minute of ischemia followed by one hour reperfusion of superior mesenteric artery caused significant elevations of MPO, catalase, MDA and nitrite levels with a significant decrease in non-protein sulfhydryls (NP-SH/ GSH) indicating an oxidative stress. These changes were significantly reversed by oral pretreatment with ORCL (200 and 400 mg/kg), suggesting that ORCL obliterates oxidative stress. Pretreatment of animals with ORCL (200 and 400 mg/kg, p.o.) or KA (100 mg/kg, p.o.), 12 and 2 hrs before the administration of 20 mg/kg indomethacin mitigated the intestinal toxicity as evidenced by decreases in tissue levels of MPO and nitrite. Unlike indomethacin, ORCL but not KA at either dose failed to induce a significant increase in intestinal permeability. This effect of ORCL simulated that of a selective COX-2 inhibitor, rofecoxib. These observations suggest that ORCL is devoid of intestinal toxicity unlike the classical non-selective COX inhibitors. Also, ORCL promoted wound healing in rats on experimental open or incision wounds as evidenced by an early wound contraction and increased wound tensile strength. The data indicate a significant anti-inflammatory potential of copaiba oil-resin and its diterpenoid, kaurenoic acid possibly mediated through an antioxidant/anti-lipoperoxidative mechanism(s).